Effectiveness of Online Single Submission (OSS) Implementation For Limited Company Legal Entities Registration By Notaries - Yalala, Nuranu; Hanim, Lathifah; Taufan, Taufan (Jurnal Konstatering, 2022)
This study was made with the aim of knowing the Effectiveness of the Implementation of Online Single Submission (OSS) for Registration of Legal Entities of Limited Liability Companies (PT) by a notary in Wonosobo Regency based on Government Regulation Number 24 of 2018 concerning Electronically Integrated Business Licensing Services. The approach method in this research is sociological juridical with descriptive research specifications. The data needed in this research includes primary and secondary data taken by observation, interviews with informants who understand, understand, and are in direct contact with the research object. The collected data is then analyzed qualitatively. Based on the research, it can be concluded that the limited liability company deed is made by a notary like other authentic deeds such as the provisions in Act No. 2 of 2914 regarding amendments to Act No. 30 of 2004 concerning the position of a notary and Article 1686 of the Civil Code with the requirements stipulated in Act No. 40 of 2207 concerning limited liability companies. In Wonosobo Regency, the online single submission system is considered ineffective because there are still confusions for legal subjects in running the system in full. Furthermore, the OSS system is considered to still tend to be weak. There are certain times when the OSS system page cannot be accessed, cannot enter the Log-In page, and a system error occurs during the issuance process of the Business Identification Number (NIB), so the user must repeat data input from the beginning again, because there is no automatic backup feature when the connection with the server is lost.